2021
DOI: 10.15252/embj.2020106272
|View full text |Cite
|
Sign up to set email alerts
|

Cellular stress promotes NOD1/2‐dependent inflammation via the endogenous metabolite sphingosine‐1‐phosphate

Abstract: Cellular stress has been associated with inflammation, yet precise underlying mechanisms remain elusive. In this study, various unrelated stress inducers were employed to screen for sensors linking altered cellular homeostasis and inflammation. We identified the intracellular pattern recognition receptors NOD1/2, which sense bacterial peptidoglycans, as general stress sensors detecting perturbations of cellular homeostasis. NOD1/2 activation upon such perturbations required generation of the endogenous metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 98 publications
1
38
0
Order By: Relevance
“…In the same direction, it is reasonable to hypothesize that cellular homeostasis dysfunction could modify host proteins or their activities and thereby activate NLRs. Indeed, generation of S1P is increased upon perturbation of cellular homeostasis and subsequently S1P triggers NOD1/2-medidated activation of innate immunity [181]. Considering that cellular homeostasis disruption induced by pathogens converges toward conserved pathways and molecules, these altered proteins/metabolites are designated as SAMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same direction, it is reasonable to hypothesize that cellular homeostasis dysfunction could modify host proteins or their activities and thereby activate NLRs. Indeed, generation of S1P is increased upon perturbation of cellular homeostasis and subsequently S1P triggers NOD1/2-medidated activation of innate immunity [181]. Considering that cellular homeostasis disruption induced by pathogens converges toward conserved pathways and molecules, these altered proteins/metabolites are designated as SAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…S1P, but not Ceramide, directly binds to NOD1 and NOD2, and S1P delivery into cells leads to NOD1 or NOD2 mediated NF-κB activation. Hence, we propose that NOD1/2 detect perturbation of cellular homeostasis through sensing of the cytosolic metabolite S1P, which represents a SAMP [181]. Whether the S1P-NOD1/2 axis is activated during infection with peptidoglycan-free pathogens needs to be elucidated.…”
Section: Nod1 and Nod2 Sense The Er Stress During Infectionmentioning
confidence: 99%
“…In non-mammalian vertebrates, NOD2 is evolutionarily conserved in fish (Nayar et al 2021) but not in reptiles (Choo et al 2019). NOD2 is primarily required for antibacterial defense but has also been implicated in antiviral defense and general sensing of perturbations of cellular homeostasis, in particular the formation of sphingosine-1-phosphate (Pei et al 2021). Recently, a drug that targets NOD2 was shown to have antiviral activity against SARS-CoV-2 and other RNA viruses (Limonta et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Humans have 5 NLRCs (NOD1, NOD2, NLRC3-5) and 14 NLRPs (NLRP1-14). The primordial function of NLRs is the detection of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), which include bacterial cell wall components, such as fragments of peptidoglycan that are sensed by NOD1 and NOD2 (Philpott et al 2014;Wolf and Underhill 2018), viral RNAs which are sensed by NOD2 and NLRP6 (Sabbah et al 2009;Wang 2015;Liu and Gack 2020), and others (Kuss-Duerkop et al 2020;Pei et al 2021). NLRs were originally identified as activators of inflammation and immune responses, but later research has demonstrated anti-inflammatory roles of several NLRs, such as NLRC3 (Li et al 2019) and NLRP12 (Williams 2005;Chen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sphingosine kinases and intracellular S1P can have differential effects on virus replication depending on the virus and the target cell. By activating NFκB via interaction with tumor necrosis factor associated factor (TRAF2; Alvarez et al, 2010 ) or NOD1/2 ( Pei et al, 2021 ), S1P also induces an inflammatory cytokine response.…”
Section: Intracellular Sphingolipid Interactions During Viral Replicationmentioning
confidence: 99%